Factors associated with uptake of home-based HIV counselling and testing and HIV care services among identified HIV-positive persons in Masaka, Uganda. Issue 7 (3rd July 2018) - Ruzagira, Eugene; Baisley, Kathy; Kamali, Anatoli; Grosskurth, Heiner
ABSTRACT: We investigated uptake of home-based HIV counselling and testing (HBHCT) and HIV care services post-HBHCT in order to inform the design of future HBHCT programmes. We used data from an open-label cluster-randomised controlled trial which had demonstrated the effectiveness of a post-HBHCT counselling intervention in increasing linkage to HIV care. HBHCT was offered to adults (≥18 years) from 28 rural communities in Masaka, Uganda; consenting HIV-positive care naïve individuals were enrolled and referred for care. The trial's primary outcome was linkage to HIV care (clinic-verified registration for care) six months post-HBHCT. Random effects logistic regression was used to investigate factors associated with HBHCT uptake, linkage to care, CD4 count receipt, and antiretroviral therapy (ART) initiation; all analyses of uptake of post-HBHCT services were adjusted for trial arm allocation. Of 13, 455 adults offered HBHCT, 12, 100 (89.9%) accepted. HBHCT uptake was higher among men [adjusted odds ratio (aOR) 1.20, 95% confidence interval (CI) = 1.07–1.36] than women, and decreased with increasing age. Of 551 (4.6%) persons who tested HIV-positive, 205 (37.2%) were in care. Of those not in care, 302 (87.3%) were enrolled in the trial and of these, 42.1% linked to care, 35.4% received CD4 counts, and 29.8% initiated ART at 6 months post-HBHCT. None of the investigated factors was associated with linkage to care. CD4 count receipt was lower in individuals who lived ≥30 min from an HIV clinic (aOR 0.60, 95%CI = 0.34–1.06) versus those who lived closer. ART initiation was higher in older individuals (≥45 years versus <25 years, aOR 2.14, 95% CI = 0.98–4.65), and lower in single (aOR 0.60, 95% CI = 0.28–1.31) or divorced/separated/widowed (aOR 0.47, 95% CI = 0.23–0.93) individuals versus those married/cohabiting. HBHCT was highly acceptable but uptake of post-HBHCT care was low. Other than post-HBHCT counselling, this study did not identify specific issues that require addressing to further improve linkage to care.